Stunned by a Heatwave: Experimental Heatwaves Alter Juvenile Responsiveness to the Threat of Predation - Merel C. Breedveld; Oliviero Borgheresi; Alessandro Devigili; Clelia Gasparini (Ecology and Evolution)
ABSTRACT Heatwaves, increasingly prevalent in our rapidly changing climate, significantly impact animals with far‐reaching ecological and evolutionary consequences. One of the first responses in animals to stress, including heat stress, is behavioural change, and this can directly influence fitness and survival. Changes in anti‐predator behaviour are particularly critical, as they may compromise a prey's ability to evade predators, thus increasing predation risk and jeopardising survival. In the context of climate change, assessing anti‐predator reactions under ecologically relevant heat stress is thus crucial, especially during the vulnerable life stage of development. This study investigated the effects of a heatwave on anti‐predator responses in juvenile guppies (Poecilia reticulata). One‐month‐old guppies were subjected to a 5‐day experimental heatwave (32°C) or a control temperature (26°C). After the treatment, all individuals were tested at a common temperature (26°C) for anti‐predator behavioural responses and swimming performance, the latter serving as a proxy for physical condition. While heatwave exposure did not affect swimming performance, it significantly altered anti‐predator responses. Heatwave‐exposed juveniles exhibited a reduced freezing response and faster resumption of normal activity compared to control fish. Our findings demonstrate that heatwaves can modify prey's anti‐predator behaviours during critical developmental stages. This suggests that heatwaves may increase predation risk, potentially impacting survival rates and reshaping predator–prey interactions in the face of ongoing climate change.